Normobaric hypoxia increases the growth hormone response to maximal resistance exercise in trained men - Filopoulos, D.; Cormack, S. J.; Whyte, D. G. (European Journal of Sport Science, 2017)
This study examined the effect of hypoxia on growth hormone (GH) release during an acute bout of high-intensity, low-volume resistance exercise. Using a single-blinded, randomised crossover design, 16 resistance-trained males completed two resistance exercise sessions in normobaric hypoxia (HYP; inspiratory oxygen fraction, (FiO2) 0.12, arterial oxygen saturation (SpO2) 82 ± 2%) and normoxia (NOR; FiO2 0.21, SpO2 98 ± 0%). Each session consisted of five sets of three repetitions of 45° leg press and bench press at 85% of one repetition maximum. Heart rate, SpO2, and electromyographic activity (EMG) of the vastus lateralis muscle were measured throughout the protocol. Serum lactate and GH levels were determined pre-exposure, and at 5, 15, 30 and 60 min post-exercise. Differences in mean and integrated EMG between HYP and NOR treatments were unclear. However, there was an important increase in the peak levels and area under the curve of both lactate (HYP 5.8 ± 1.8 v NOR 3.9 ± 1.1 mmol.L-1 and HYP 138.7 ± 33.1 v NOR 105.8 ± 20.8 min.mmol.L-1) and GH (HYP 4.4 ± 3.1 v NOR 2.1 ± 2.5 ng.mL-1 and HYP 117.7 ± 86.9 v NOR 72.9 ± 85.3 min.ng.mL-1) in response to HYP. These results suggest that performing high-intensity resistance exercise in a hypoxic environment may provide a beneficial endocrine response without compromising the neuromuscular activation required for maximal strength development.